STRATEGI PEMBERDAYAAN SUMBER DAYA MANUSIA MELALUI KEGIATAN DAKWAH DAN MEDIA DIGITAL - Nurjanah; Sobirin; Sofia Maqom Al Mahmudah; Rizky Almufid Anshori (STKIP Subang, 2024)
Da'wah, as the activity of conveying Islamic teachings, plays a crucial role in building the moral and character of society. In the digital era, the use of digital media in da'wah has become increasingly relevant to reach a broader audience and leverage technology as an effective communication tool. Human resource empowerment through da'wah and digital media not only involves the delivery of religious messages but also aims to enhance individual knowledge, skills, and ethics within social and professional environments. This study discusses strategies for human resource empowerment through da'wah and digital media activities to improve individual quality and capacity. Digital da'wah has become an effective means to disseminate religious teachings and ethics, which can support human resource character development. This article aims to analyze human resource empowerment strategies through da'wah and digital media and to identify challenges faced in its implementation. The method used is a literature review and secondary data analysis relevant to the topic. The study results indicate that the integration of da'wah and digital media can accelerate the process of empowering human resources with greater integrity, productivity, and high moral values. Keywords: Human Resource Empowerment, Da'wah, Digital Media, Strategy.